A Novel Configuration of A Microstrip Power Amplifier based on GaAs-FET for ISM Applications - Amine Rachakh; Larbi El Abdellaoui; Jamal Zbitou; Ahmed Errkik; Abdelali Tajmouati; Mohamed Latrach (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Power Amplifiers (PA) are very indispensable components in the design of numerous types of communication transmitters employed in microwave technology. The methodology is exemplified through the design of a 2.45GHz microwave power Amplifier (PA) for the industrial, scientific and medical (ISM) applications using microstrip technology. The main design target is to get a maximum power gain while simultaneously achieving a maximum output power through presenting the optimum impedance which is characteristically carried out per adding a matching circuit between the source and the input of the power amplifier and between the load and the output of the power amplifier. A "T" matching technique is used at the input and the output sides of transistor for assure in band desired that this circuit without reflections and to obtain a maximum power gain. The proposed power amplifier for microwave ISM applications is designed, simulated and optimized by employing Advanced Design System (ADS) software by Agilent. The PA shows good performances in terms of return loss, output power, power gain and stability; the circuit has an input return loss of -38dB and an output return loss of -33.5dB. The 1-dB compression point is 8.69dBm and power gain of the PA is 19.4dBm. The Rollet's Stability measure B1 and the stability factor K of the amplifier is greater than 0 and 1 respectively, which shows that the circuit is unconditionally stable. The total chip size of the PA is 73.5× 36 mm2.